Optimasi Kualitas Animasi “Generate” melalui Video Referensi Menggunakan Metode Pose to Pose - Zega, Selly Artaty; T. Deepa (Politeknik Negeri Batam, 2025)
This study aims to optimize the quality of the 3D animated short film “Generate” by applying the pose-to-pose animation method supported by the effective use of reference videos. Previously, the animation was done using the straight-ahead technique, which was considered ineffective in highlighting key poses, timing, and arcs. Through an experimental qualitative approach, the animation was improved using the pose-to-pose method, which included analyzing reference videos to determine the correct key poses, breakdowns, and in-betweens. The resulting animation was then validated by professional animation practitioners based on aspects of timing, arcs, and overall visual quality. The findings showed a significant improvement in the clarity of the animation, arcs, and character poses. The pose-to-pose method is also considered effective for novice animators because it provides a more structured workflow to support staging and storytelling. However, challenges remain in the ability to accurately understand and apply references, requiring more in-depth training. This study offers a practical framework that can bridge the animation learning process in an academic environment with professional industry standards.